2017
DOI: 10.1155/2017/2032697
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Genistein against Mono-(2-ethylhexyl) Phthalate-Induced Oxidative Damage in Prepubertal Sertoli Cells

Abstract: Mono-(2-ethylhexyl) phthalate (MEHP) and genistein are two of the most prevalent endocrine-disrupting chemicals (EDCs) that present in the environment and food. However, how these two EDCs would affect prepubertal Sertoli cells development was rarely studied. In this study, primary prepubertal Sertoli cells were isolated from 22-day-old Sprague Dawley rats and exposed to MEHP at 1 μmol/L, 10 μmol/L, and 100 μmol/L (M1, M10, and M100), genistein at 10 μmol/L (G), and their combination (G + M1, G + M10, and G + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…30 Previous studies have investigated the role of genistein in brain injury and found that genistein has significant anti-inflammatory and anti-oxidative properties. [31][32][33] However, the poor water solubility of genistein restricted its wide use in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…30 Previous studies have investigated the role of genistein in brain injury and found that genistein has significant anti-inflammatory and anti-oxidative properties. [31][32][33] However, the poor water solubility of genistein restricted its wide use in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment of neonatal rats with low levels of di (2-ethylhexyl) phthalate (DEHP) and its metabolite, MEHP, induces a decrease in Sertoli cell proliferation accompanied by a decrease in cyclin D2 levels (306). More recently, it has been shown that MEHP can disrupt prepubertal Sertoli cell proliferation by increasing intracellular ROS levels (307). On the other hand, it has been shown that another plasticizer of the phthalate family, mono-n-butyl phthalate (MBP), induces immature Sertoli cell proliferation up-regulating ERK1/2 signaling pathway (308).…”
Section: Pharmacological Agents and Xenobiotics May Affect Sertoli Cementioning
confidence: 99%
“…Increased cytokines, such as TNF-α and IL-6, are hallmarks of many human inflammatory states, including sepsis [30,31]. Previous data have suggested protective effects of genistein such as antitumor, antioxidative, and antiapoptotic functions [32][33][34]; however, the anti-inflammatory effect of GSS, a new compound derived from genistein, is still incompletely understood. In the present study, we demonstrated that the GSS was able to inhibit LPS-induced lung microvascular EC injury and sepsis-induced ALI.…”
Section: Discussionmentioning
confidence: 99%